Twitter Sebagai Media Propaganda (Analisis Wacana pada Tweet @TsamaraDKI dan @FaldoMaldini sebagai Media Propaganda Menjelang Pemilihan Presiden 2019) - Sahlan Marzuuqi; Muchamad Yulianto (Interaksi Online, 2019)
Political propaganda is one of the ways that politicians use to bring opinions and issues that are developing in society ahead of the 2019 Political elections. The purpose of political propaganda is none other than to get support and win votes in a political contestation. Social media is one tool that is often used to convey propaganda. Twitter social media platform is the right choice for politicians to convey their political propaganda. Tsamara Amany Alatas and Faldo Maldini are young Indonesian politicians who are active in using social media twitter. Both are part of each winning team of candidates for president and vice president who advanced in political contestation in 2019. Although newcomers, both politicians have influence in the Indonesian political arena which is quite strong supported by their active use of social media. This research uses Discourse Analysis which after analysis is associated with political propaganda. The results of the research using discourse analysis can be seen the forms and propaganda techniques issued by the Twitter account politicians @TsamaraDKI and @ FaldoMaldini ahead of the 2019 presidential and vice presidential elections, namely using propaganda techniques of name calling, glittering generalities, card stacking, plain folks, bandwagon techniques, testimonials